[PP.33.12] THE INFLUENCE OF ANTIHYPERTENSIVE TREATMENT ON THE FUNCTION OF LEFT VENTRICLE IN PATIENTS WITH PRIMARY, UNCOMPLICATED HYPERTENSION. (September 2016) - Pizon, T.; Rajzer, M.; Rojek, M.; Czarnecka, D.
Abstract : Objective: The aim of the study was to check if chosen antihypertensive drugs can influence the ejection fraction of left ventricle (EF) and to assess possible factors for this change. Design and method: 95 never treated patients with HT stage 1 or 2 were randomized to 6 months monotherapy with: quinapril, amlodipine, hydrochlorothiazide, losartan or bisoprolol. Each therapeuthic group consisted of 19 patients (N=19). Before and then after 1, 3 and 6 months of treatment EF in echocardiography, arterial stiffness indexes: carotid-femoral pulse wave velocity (PWV) by using COMPLIOR device and aortic pulse pressure (AoPP) from pulse wave in applanation tonometry by using SPHYGMOCOR device were measured. Results: At baseline no differences between groups were observed in EF. ANOVA for repeated measurements revealed for all groups significant increase in EF (p = 0.01). No differences appeared between therapeutic groups in mentioned above effect. PWV and AoPP decreased significantly during observation period in all examined groups (p value: 0.0007 and 0.0003 respectively), with no between-groups difference. Conclusions: Irrespectively of chosen drug we observed similar effect for EF increase; PWV and AoPP decrease drop. Improvement of left ventricle function as a result of antihypertensive therapy is strongly connected with arterial stiffness decrease.